2003
DOI: 10.1111/j.1834-7819.2003.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine eruption into grafted alveolar clefts: A retrospective study

Abstract: Background: The contemporary treatment of cleft lip and palate involves a sequence of surgical procedures and orthodontic management. Alveolar bone grafting (ABG) is usually undertaken after orthodontic expansion of the maxillary segments between the ages of eight and 12 years. Two of the important goals of alveolar bone grafting are the provision of bony support for the eruption of the canine and the closure of residual oro-nasal fistulae. The purpose of this study was to retrospectively evaluate the root dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 14 publications
1
23
3
3
Order By: Relevance
“…Interestingly, permanent canine retention was recorded in 15.5 percent of the sample and a surgical exposure of the canines was recorded in 4.4 percent of the sample (Table 3). Our percentage of retention seems higher than that reported after secondary bone grafting by other authors (e.g., 10 percent, 32 8 percent, 33 35 ), we believe the early closure of the alveolus compared with the timing of bone grafting might cause the reduction of the alveolar bone space at the cleft area, as suggested by Berkowitz et al 11 This partial reduction of the alveolar space might therefore be responsible for the higher percentage of canine retention. Over 70 percent of the patients had an orthodontic expansion of some extent.…”
Section: Permanent Dentitioncontrasting
confidence: 81%
“…Interestingly, permanent canine retention was recorded in 15.5 percent of the sample and a surgical exposure of the canines was recorded in 4.4 percent of the sample (Table 3). Our percentage of retention seems higher than that reported after secondary bone grafting by other authors (e.g., 10 percent, 32 8 percent, 33 35 ), we believe the early closure of the alveolus compared with the timing of bone grafting might cause the reduction of the alveolar bone space at the cleft area, as suggested by Berkowitz et al 11 This partial reduction of the alveolar space might therefore be responsible for the higher percentage of canine retention. Over 70 percent of the patients had an orthodontic expansion of some extent.…”
Section: Permanent Dentitioncontrasting
confidence: 81%
“…The timing of the operation is based on radiographic images of the unerupted cuspid adjacent to the cleft, whereby the root has to be 50% to 75% formed (el Deeb et al, 1989;da Silva Filho et al, 2000;Hogan et al, 2003;Gereltzul et al, 2005;Matsui et al, 2005).…”
Section: Surgical Treatment Protocolmentioning
confidence: 99%
“…Case #4 also used AutoBT as grafting material in reconstructing alveolar cleft defects to guide the normal eruption of maxillary right canine. Studies have demonstrated that restoring alveolar cleft from the crest of the alveolus to the base of the nose early in the developmental stage of maxillary canine promotes normal eruption through the grafted area [12][13][14] . Although the recommended time in alveolar bone grafting is controversial, secondary bone grafting in mixed dentition is normally done between the ages of 9 and 11 when the canine root is one-fourth to two-thirds developed 13) .…”
Section: Discussionmentioning
confidence: 99%